2014
DOI: 10.1038/bjc.2014.253
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD44 variant 2 upregulation in colorectal cancer

Abstract: Background:CD133 and CD44 are putative cancer stem cell (CSC) markers in colorectal cancer (CRC). However, their clinical significance is currently unclear. Here, we evaluated primary CRC cell isolates to determine the significance of several CSC markers, including CD133 and CD44, as predictors of tumourigenesis and prognosis.Methods:CD133- and CD44-positive cells from fresh clinical samples of 77 CRCs were selected by flow cytometric sorting and evaluated for tumourigenicity following subcutaneous transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
(39 reference statements)
3
43
0
Order By: Relevance
“…Similar observations were made in non-small cell lung cancer [74]. However, another report showed that patients with colorectal cancer with high expression of CD44v2 had a poorer prognosis than patients with other CD44v isoforms [75]. The discrepancy in prognostic value between CD44s and CD44v isoforms among different reports and in different tumor types awaits further clarification.…”
Section: Clinical Significance Of Cd44 In Cancer Cd44 As a Valuable Bsupporting
confidence: 64%
“…Similar observations were made in non-small cell lung cancer [74]. However, another report showed that patients with colorectal cancer with high expression of CD44v2 had a poorer prognosis than patients with other CD44v isoforms [75]. The discrepancy in prognostic value between CD44s and CD44v isoforms among different reports and in different tumor types awaits further clarification.…”
Section: Clinical Significance Of Cd44 In Cancer Cd44 As a Valuable Bsupporting
confidence: 64%
“…Anti‐CD44 exon 10 antibody blocked metastasis . Patients having colorectal cancer with high expression of CD44 exon 6 had a poor prognosis . This study identified a novel splicing isoform, CD44v, which does not have exon 8 and 9.…”
Section: Discussionmentioning
confidence: 84%
“…CD44 and activation of WNT, NOTCH1 increases aggressiveness, correlating with progression in colon cancer . CD133 is also associated with enrichment of undifferentiated cells and tumorigenic behavior along with its implication in epithelial dedifferentiation . NOTCH1 signaling has been correlated with normal epithelial differentiation of squamous cells; exogenous expression of the Notch‐Intracellular domain (NICD) enhanced the proliferation/self‐renewal of the head and neck cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 CD133 is also associated with enrichment of undifferentiated cells and tumorigenic behavior along with its implication in epithelial dedifferentiation. 43,44 NOTCH1 signaling has been correlated with normal epithelial differentiation of squamous cells 45 ; exogenous expression of the Notch-Intracellular domain (NICD) enhanced the proliferation/ self-renewal of the head and neck cancer cells. In our study, Notch1 was deregulated in the epithelial cell lines and an inhibition of its activity using GSI led to a significant decrease in CSC and dysplastic profile, indicating its significance in dysplastic progression of oral cancer.…”
Section: Discussionmentioning
confidence: 99%